Behavioral Measures of Saccade Latency and Inhibition in Manifest and Premanifest Huntington’s Disease - Turner, Travis H. (2011)
Initiation and inhibition of saccadic eye movements has been shown to be impaired in patients with Huntington’s disease (HD) and premanifest gene carriers (PMGC), and may provide biomarkers useful in tracking phenotypic change. Computerized behavioral tests of prosaccade latency and disinhibition presented to 31 non–gene carriers (NGC), 25 PMGC, and 12 HD patients. These tests provided quantitative performance measures without use of eye-tracking equipment. Significant differences on saccade tests were found, with PMGC intermediate between NGC and HD patients. Saccade latency discriminated PMGC from NGC, whereas saccade disinhibition discriminated PMGC from HD patients. Results suggest utility of behavioral saccade measures as premanifest indicators of phenoconversion in HD.